Nurturing Tradition, Embedding Local Islam: The Existence of the Besaprah Tradition in Sambas Malay Society - Jaelani, Jaelani; Risa, Risa; Trisnawati, Hikmah (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2025)
Globalization presents significant challenges to the existence of local wisdom, including the Besaprah tradition in Sambas Malay society. Therefore, this article aims to examine Besaprah as a dynamic and adaptive cultural practice that lies at the intersection of Sambas’ Malay cultural identity, local Islam, and efforts to maintain its existence amid social change and modernity. This study uses qualitative methods, including an oral history approach, and draws on document and literature reviews, as well as in-depth interviews with religious, traditional, and community leaders. Data were collected between April and May 2021, and sources were verified and analyzed using cultural history theories and concepts. The results show that Besaprah is an expression of the cultural identity of the Sambas Malay and a symbol of Islamic teachings, egalitarian values, social solidarity, and modesty. Support from religious and traditional leaders, state recognition through registration as Intangible Cultural Heritage (WBTb), and cultural festivals are methods used to preserve this tradition. In conclusion, Besaprah is an adaptive and dynamic cultural practice that helps the Sambas Malay community preserve its cultural identity, embody Islamic principles, and enhance social cohesion.